A Pilot Study to Validate the Burn Center Pediatric Early Warning Score Tool in Clinical Practice. Issue 3 (May 2016) - Rahman, Zahra H.; Leahy, Nicole E.; Sessler, Kelly; Greenway, Andrew; Sorensen, Logan; Breznak, Kara; Rabbitts, Angela; Macklay, Holly; Yurt, Roger W.
Abstract : The pediatric early warning score (PEWS) tool helps providers to detect subtle clinical deterioration in non–intensive care unit pediatric patients and intervene early to prevent significant adverse outcomes. Although widely used in general pediatrics, limited studies report on its validation; none report on use with burn-injured patients. New York-Presbyterian/Weill Cornell Medical Center modified a general PEWS system to a burn-specific PEWS and integrated its use into standard practice. This study investigated the external validity of the PEWS process in clinical practice. Fifty cases of patients aged 0 to 15.9 years admitted between January 2012 and June 2013, whose length of stay (LOS) more than 3 days were selected for review from this cohort of n equal to 187. Demographics, total PEWS and score changes, and compliance with PEWS documentation and with resultant interventions were reviewed. Continuous variables are presented as mean ± SD, P less than 0.05. Mean age, burn size, and LOS were 3.2 ± 3.3 years, 4.8 ± 5.7%, and 9.8 ± 7.0 days; 26% required grafting, and 50% were male. No mortalities occurred. One thousand six hundred and twelve PEWS from 1745 opportunities were documented (92.4%). For all PEWS (n = 1612) and PEWS greater than 0 (n = 912), means were 0.9 ± 1.2 and 1.6 ± 1.2, respectively. Among the 162 PEWS increase events, intake (54.1%) and output (4.5%) parameters increased most commonly. Of these, 129 PEWS increases (79.6%) were followed by an intervention that most commonly included text notation of score increase (93.7%), physician/physician assistant notification (70.5%), and feeding-tube insertion (25.6%). Patients with PEWS greater than 0 had similar age, LOS, and larger burn size (5.2% vs 1.4%, P < 0.05) than those with PEWS equal to 0. Compliance with PEWS performance and resultant actions based on score increases are high. Data support that even small changes in burn-injury specific PEWS stimulate provider discussion and intervention and support its validation; further studies on its effect on practice are warranted.